Il principio di formalità adeguata nel procedimento di formazione degli atti amministrative nel diritto canonico - Canosa, Javier (2010)
The procedural modalities established in canon law are instruments of justice not only in the ambit of the canonical process. The necessity of procedural formality is particularly relevant in canonical administrative law
Keywords: Verwaltungsrecht; Verwaltungsverfahren; Verwaltungsakt; Kanonisches Recht; Allgemeine Normen